2007
DOI: 10.4161/hv.3.4.4058
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies from Women Immunized with Gardasil ® Cross-Neutralize HPV 45 Pseudovirions

Abstract: Human papillomavirus (HPV) types 6, 11, 16 and 18 L1 virus-like particles (VLPs) have been used to generate the prophylactic quadrivalent vaccine, Gardasil ® . There is a high degree of L1 homology between HPV types and it is likely that there is a substantial degree of surface exposed viral epitope similarity. An investigation of vaccine-induced antibody binding and neutralization was undertaken focusing on A7 species members, HPV 18 and 45. Polyclonal sera from Gardasil ® recipients and from HPV 18 L1 VLP re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 38 publications
2
78
0
6
Order By: Relevance
“…1, although immunization with existing vaccines would cover more than 50% of infections, a high percentage (45.3%) of HR-HPV infections would not be prevented by these vaccines. Although the cross-protection data are encouraging 16,30 , the titers of the neutralizing antibodies for the genotypes not included in the formulation are about ten times lower than those for the genotypes that are included. This generates uncertainty about whether they will disappear more rapidly than the specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, although immunization with existing vaccines would cover more than 50% of infections, a high percentage (45.3%) of HR-HPV infections would not be prevented by these vaccines. Although the cross-protection data are encouraging 16,30 , the titers of the neutralizing antibodies for the genotypes not included in the formulation are about ten times lower than those for the genotypes that are included. This generates uncertainty about whether they will disappear more rapidly than the specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the protection against HPV 52 and HPV 58 (two of the four most frequent HR-HPV in our study) is not significant. These data have led some authors to infer that the cross-protection seems to be limited 27,30 .…”
Section: Discussionmentioning
confidence: 99%
“…46,47 The H18.R5 antibody has been shown to recognize both HPV 18 and HPV 45 conformational VLPs and neutralize both A7 species members. 46,48 This observation suggests variability between HPV types in utilization of immunodominant epitope on L1 VLPs. Thus, some women may make highly efficient, neutralizing antibodies to epitopes on HPV 18 VLPs that differ from the HPV 18 type-specific epitope monitored in the cLIA by H18.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 95%
“…Structural alterations of the external surface topography of L1 can be conferred by minor sequence differences between genotypes (13), supporting observations that almost all neutralizing monoclonal antibodies (MAbs) that target these external surfaces are type specific (14)(15)(16)(17). Nevertheless, functional antibody cross-reactivity is a common feature of sera from recipients of the Cervarix (bivalent) and Gardasil (quadrivalent) vaccines (18)(19)(20)(21)(22) and may be responsible for conferring HPV vaccine-induced cross-protection (23).…”
Section: ϫ8mentioning
confidence: 90%